Didactic proposal for teaching basic electrical circuits - León, Luis Fernando Parra; Duarte, Julio Enrique; Morales, Flavio Humberto Fernández (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This paper reports a methodological approach to teach basic electrical circuits, based on the constructivist model and two of their variants: meaningful learning and collaborative learning. Applying the DIRECT test it was evaluated the hability of analizing electrical circuits of direct current, by future technology teachers at the UPTC, formed with the tradicional model. Due to the bad results, it is proposed a methodology as a teacher guide, the didactic strategy is planned around three working guides inn which are included individual and groupal activities, besides the solution of real problems.